Democratic Citizenship, Critical Multiculturalism, and the Case of Muslims Since September 11 (In Factis Pax: Journal of Peace Education and Social Justice, 2011)
Key to democratic citizenship is understanding in a basic sense other people and groups in society. In the United States there has been a lively debate regarding howeducators and students should set about doing this, however—how they should respond to differences from mainstream norms, inside and outside their classrooms, and the presence of minorities in society. In this essay, I want to illuminate specific aspects of the challenges public school educators face in constructively and accurately teaching about controversial groups in their classrooms by exploring the case of educating about Muslims since September 11 (9/11). I argue that in this particular instance the ability of multicultural educators1 to provide students with accurate, balanced understandings of the religion and group is hindered by limitations internal to the traditional approaches to multicultural education in the United States, as well as by expectations set by current educational standards and related constraints set by typical teacher education programs.